Principal component analysis of equatorial geomagnetic & ionospheric diurnal variations - Rangarajan, G. K. (My University, 1996)
Mean diurnal variations of the H and D components of the geomagnetic field and the Total Electron Content (TEC) at selected stations, close to the dip equator, at low latitude away from the equatorial electrojet influence and close to the latitude of the Sq focus are examined through the method of Principal Component Analysis for strong electrojet, weak electrojet and counter electrojet days. It is shown that the strength of the electrojet influences H and D variations at even higher latitudes largely through the second principal component. For D, in particular, the first component is shown to be largely unaffected by the changes in the electrojet strength.
Keywords: Principal components; Equatorial electrojet; Counter electrojet; Total electron content